Minimising OHSS in women with PCOS - Leathersich, Sebastian; Roche, Caitlin; Hart, Roger (Frontiers in Endocrinology, 2025)
Ovarian hyperstimulation syndrome (OHSS) is a serious iatrogenic complication of ovarian stimulation during in vitro fertilisation (IVF) treatment and is associated with significant morbidity and a small risk of mortality. Women with polycystic ovary syndrome (PCOS) are at a substantially increased risk of developing OHSS compared to those without. This paper reviews the current evidence for strategies to mitigate the risk of OHSS in this patient population. In order to minimise the risk of OHSS, clinicians should identify patients at high risk prior to commencing treatment and provide adequate pre-treatment counselling regarding the risks and benefits of IVF treatment, as well as alternative treatment options. Strategies that can reduce the risk of OHSS include co-treatment with metformin in gonadotropin releasing hormone (GnRH) agonist cycles, use of GnRH antagonist or PPOS protocols, appropriate gonadotropin dosing, the use of a GnRH agonist trigger for oocyte maturation in antagonist or PPOS protocols, cryopreservation of all embryos with deferred frozen embryo transfer, and treatment with dopamine-agonists after oocyte collection. In vitro maturation (IVM) offers an alternative with no risk of OHSS, however currently has a lower cumulative live birth rate than conventional IVF. These strategies can prevent significant early and late OHSS in women with PCOS and should be used to optimise the safety of IVF for this high-risk population, striving for OHSS-free treatment for all patients undergoing IVF.